Microleakage Evaluation in Class V Cavities Restored with Five Different Resin Composites: In vitro Dye Leakage Study [Corrigendum] - Bajabaa S; Balbaid S; Taleb M; Islam L; Elharazeen S; Alagha E (Dove Medical Press, 2021)
Bajabaa S, Balbaid S, Taleb M, Islam L, Elharazeen S, Alagha E. Clin Cosmet Investig Dent. 2021;13:405–411. The authors have advised there is an error in the author list on page 405. The author name “Shaza Balbaid” should read “Shatha Balbaid”. The authors apologize for this error. Read the original article